Testing a structural model for study demands and resources, study engagement and well-being of first-year university students. Issue 3 (3rd May 2020) - Luruli, Khumbudzo; Mostert, Karina; Jacobs, Melissa
Abstract : This study investigated the relationships between study demands, study resources, engagement, and subjective well-being (including social-, emotional- and psychological well-being) for first-year university students. The students ( n = 773; females = 65.7%; black = 60.7%; mean age = 20.24, SD = 2.71) completed the following measures: the Student-Stress Questionnaire (SSQ), an adapted version of the Questionnaire on the Experience and Assessment of Work (QEAW), the Utrecht Work Engagement Scale-Student Survey (UWES-S) and the Mental Health Continuum-Short Form (MHC-SF). Structural equation modelling analysis of the data showed students who perceived higher academic demands also self-reported a lower sense of engagement with their studies. Those who perceived to be supported by lecturers and with a high sense of autonomy, self-reported higher engagement with their studies. Students who self-perceived personal relationship problems or high personal relationship demands also self-reported lower social, emotional, and psychological well-being. Students who perceived social support from friends and family and who self-reported high levels of autonomy, had psychological well-being. Engagement mediated the relationship between study demands, study resources and well-being. Perceived study demands and study resources by students are important to student counselling and development services to assist students' quality of life at university.